Emergency temporary standards and COVID-19 trends among Oregon farmworkers - Raul Cruz-Cano; Devon C. Payne-Sturges (PLoS ONE, 2025)
Background During the COVID-19 pandemic, migrant and seasonal farmworkers were deemed essential due to their central roles in US agricultural operations. However, employer-provided housing and transportation conditions increased their risks of SARS-CoV-2 exposure, and some states implemented emergency temporary standards (ETSs) at the insistence of farmworker advocates. Despite numerous studies examining the effectiveness of policy interventions (e.g., workplace closures) for mitigating SARS-CoV-2 transmission, limited research has specifically examined the effectiveness of interventions aimed at protecting farmworkers from COVID-19. Methods We used an interrupted time series analysis to estimate how two ETSs and one executive order issued in Oregon impacted COVID-19 trends from March 1, 2020, to February 27, 2021, for the overall population and among agricultural labor groups in Oregon. Results Our models show that the ETS and executive order, which specifically targeted farmworker housing, transportation, and worksites, did not demonstrate any significant effects on the numbers of COVID-19 cases or associated deaths. However, the other ETS, which targeted all workplaces, was associated with statistically significant decreases in COVID-19 cases among the general population (−142.36214, p-value<0.0001), producers (−1.67128, p-value = 0.0009), hired workers (−2.39413, p-value = 0.0014), unpaid workers (−1.01572, p-value = 0.0003), and migrant workers (−0.60017, p-value = 0.0166). None of the three policy changes were found to have any statistically significant impacts on the numbers of COVID-19–associated deaths. Conclusions The ETS targeting all workplaces was more effective for reducing COVID-19 transmission than the ETS or executive order specifically targeting farmworkers, indicating that the design, communication, and implementation of ETSs targeting farmworkers should be re-evaluated.